“EU TENHO UM AMBIENTE MARAVILHOSO, MAS EU TENHO UM AMBIENTE ENORME DE INCERTEZAS”: prazer e sofrimento no trabalho no contexto das startups - OLIVEIRA, Heitor Natividade (2017)
It was investigated the pleasure-suffering dynamics on professionals’ daily labor who work at startups from São Luís, MA, by characterizing routine activities and labor relations in these companies, by identifying the elements that generate pleasure and/or suffering, and by analyzing the mediation strategies implemented by the workers in order to cope adversity. In order to do so, three companies with characteristics that allowed identifying them as startups were selected and semi-structured interviews were conducted with seven professionals acting in this field, which five were entrepreneurs or managers and two were workers. Psychodynamics of Work was used as theoretical reference, that recognizes the forms of work organization as core to the understanding of pleasure and suffering dynamic, situating them in the historical and social context in which they occur. Psychodynamics of Work also considers the possible destinies of suffering, whether its re-signification by the use of practical intelligence and subjective mobilization or illness due the exhaustion of defense strategies. The main sources of demonstrated satisfaction were the incentive to the use of creativity and innovation, enjoyable atmosphere and the recognition. However, there was an intensification of the contradictions of toyotist model, such as precarization of employment bonds, false freedom provided by technology and by flexibility of time and workplace. Unrestricted adherence to the purposes and ideals of the companies, evidenced by the terms alignment and engagement was also noted. The atmosphere of extreme uncertainty of startups and sensations caused by it such as insecurity, fear, stress and anxiety were especially highlighted. Defensive strategies used to deal with such consequences, such as the negation of work overload and the rationalization expressed by euphemizing of suffering were identified. Such defenses and others have been shared by all interviewees so frequently that they may be interpreted as a defensive ideology. Finally, the requirement level regarding to the profile of professionals, who need to present heroic contours to withstand the adversities of such conjuncture was observed.